2008
DOI: 10.1017/s1751731108002966
|View full text |Cite
|
Sign up to set email alerts
|

Percentile growth charts for biomedical studies using a porcine model

Abstract: Increasing rates of obesity and heart disease are compromising quality of life for a growing number of people. There is much research linking adult disease with the growth and development both in utero and during the first year of life. The pig is an ideal model for studying the origins of developmental programming. The objective of this paper was to construct percentile growth curves for the pig for use in biomedical studies. The body weight (BW) of pigs was recorded from birth to 150 days of age and their cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Firstly, in larger animals, the reserve zone, which is mainly comprised of dense extracellular matrix and is the stiffest region of the growth plate, takes 70% of the total volume at the newborn stage (Sergerie et al 2009) and gradually decreases in size with age (data not shown). Secondly, a high rate of growth as indicated by rapid weight gain (Corson et al 2008), particularly toward the pubertal stage, is associated with increased cellular hypertrophy (Alexander 1976). As the hypertrophic zone is the weakest zone of the growth plate, the consequent increase in cell/matrix volume ratio could also explain the observed decrease in stiffness with developmental stage (Sergerie et al 2009;Mehlman and Koepplinger 2010).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in larger animals, the reserve zone, which is mainly comprised of dense extracellular matrix and is the stiffest region of the growth plate, takes 70% of the total volume at the newborn stage (Sergerie et al 2009) and gradually decreases in size with age (data not shown). Secondly, a high rate of growth as indicated by rapid weight gain (Corson et al 2008), particularly toward the pubertal stage, is associated with increased cellular hypertrophy (Alexander 1976). As the hypertrophic zone is the weakest zone of the growth plate, the consequent increase in cell/matrix volume ratio could also explain the observed decrease in stiffness with developmental stage (Sergerie et al 2009;Mehlman and Koepplinger 2010).…”
Section: Figmentioning
confidence: 99%
“…This difference in mechanical properties may be attributed to rapid porcine developmental changes at the 3-4 week period, where it was shown that pigs experience an increase in growth at 3 weeks followed by a decrease at 4 weeks. Indeed, between 2 and 3 weeks, pigs increase by about 60% in mass, followed by a 20% decrease between 3 and 4 weeks (Davies et al 1984;Corson et al 2008). Bone growth is directly stimulated by increased levels of testosterone and decreased levels of estrogen due to the presence of receptors within the growth plate, or indirectly by stimulating growth hormone that increases cellular proliferation (Peralta et al 1994;Maor et al 1999;Juul 2001;Phillip et al 2001;Van der Eerden et al 2002;Irie et al 2005;Savendahl 2005;Chagin and Savendahl 2007).…”
Section: Figmentioning
confidence: 99%
“…,10th percentile: generation 1 (G1) L; n 5 4) and the heaviest (G1 N; n 5 4) female piglets from each litter were selected to enter the generation study. It should be noted that although the heaviest female pigs in each litter were selected, their birth weight did not exceed the 90th percentile for weight for our normal population of pigs (Corson et al, 2008) and so they were classified as normal birth weight pigs (i.e. .20th , 80th percentile for body weight).…”
Section: Animals and Dietmentioning
confidence: 99%
“…Given that glucose is the main energy substrate for foetal metabolism (Battaglia and Meschia, 1978), it seems feasible that mothers who themselves were SGA would exhibit poor glucose homoeostasis in pregnancy, leading to a reduction in reproductive performance. Indeed, it has been demonstrated that glucose curve characteristics following a glucose tolerance test (GTT) in late pregnancy can, to some extent, be used to predict total litter performance of sows (Kemp et al, 1996;Corson et al, 2008). It remains to be established whether glucose tolerance in the pre-pregnant state can also be used as a reliable indicator of reproductive performance, thus supporting the intrauterine programming hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Percentile growth curves have been widely used in many medical and health care areas for humans [9, 12, 15, 22, 24, 25] and animals [4, 13]. The construction of percentile growth curves has been investigated for Thoroughbred horses [5, 11], where percentile body weight charts for Thoroughbreds were available.…”
mentioning
confidence: 99%